Akademi Infotech Mara (AIMAS) Intranet Learning Portal : A Prototype - Mohd. Taufik, Alias (2003)
Electronic Learning (E-Learning) is one of the studying techniques, which is growing rapidly in the higher institution such as universities and colleges. E-Learning is developed and implemented through the web application form as it is beneficial while using it. The progress of developing E-Learning portal are to reduce paper consumption, develop good relationship and networking among lecturers, administration staff and students of Akademi Infotech MARA Alor Setar (AIMAS), simplify the learning and disseminating of knowledge/ information by the lecturer. Methodology used in developing the prototype system is Rapid Application Development (RAD), which comprises of 4 phases such as analysis, design, development and implementation. Database used to develop the system is MySQL with PHP programming language. Apache server is used as the server to run the system and Internet Explorer 6.0 as a web browser of the system. The benefit could be acquired by using this portal is users may apply it at anywhere in AIMA’S building. Through the creation of this portal, lecturer would be able to reduce cost and time consumption in providing notes, quizzes, information and project to students.